Iron-rich microband formation in marine sediments by hydrothermal iron cycling bacteria at Lucky Strike− - Jérémie Aubineau; Ernest Chi Fru; Christine Destrigneville; Thierry Decrausaz; Fleurice Parat; Fabien Baron; Alexandra Nederbragt; Manuel Henry; Alain Castillo; Céline Rommevaux; Valérie Chavagnac (Communications Earth & Environment)
Abstract Models describing banded iron formation deposition beneath oxygenated Paleoproterozoic marine shelf waters assume that microaerophilic iron-oxidizing microorganisms were significant contributors. However, direct evidence for this mechanism is lacking, and it remains unclear how associated primary organic biomass and biogenic iron oxyhydroxides transformed into organic carbon-poor iron oxide/carbonate-rich bands in banded iron formations. Here we explore in situ modern Zetaproteobacterial iron-oxidizing mats thriving in the Lucky Strike hydrothermal vent field to develop an empirical model that explains the potential contribution of iron-based metabolisms to deposition of rocks resembling banded iron formations. Petrographic, mineralogical, and geochemical data suggest that abundant production of Zetaproteobacterial stalks nucleates and drives spontaneous biotic/abiotic ferrihydrite precipitation in the mats. Subsequent early diagenetic anaerobic microbial oxidation of dead biomass as the mats aged, coupled to microbial reduction of iron oxyhydroxides/oxides, generates ferrous carbonates and mixed valence magnetite. Collectively, this forms crystalline iron-rich organic carbon-lean 13C-depleted layers reminiscent of Precambrian banded iron formation microbands.